Chapter 7 Transfiguration - Vilar, Márcio (Taylor & Francis, 2024)
The Routledge Handbook of Religion and the Body is the first comprehensive volume to feature multireligious cross-cultural perspectives on the body and embodiment. Featuring multidisciplinary approaches and methodologies from the humanities and the social sciences, it addresses the body and embodied religiosity in theological, ethical, and cultural contexts. Comprised of 30 chapters by a team of international contributors, the handbook is divided into four parts: Theology and Embodied Religiosity Gender, Sexuality, and Body Regulations Ritual and Performance Religion, Healing, and the Future of the Body Each part examines central issues, debates, and problems in relation to global belief systems, including embodiments of love, transfiguration, the secular body, disability, body language, maternal bodies, embodied emotions, celibacy, ecology and the body, reshaping the corporal body, initiation rites, physiology, Tantra, Reiki practice, religious experience, technological body modifications, and ethics and the body. Providing a breadth of rich and innovative research, it is a must-read for students and scholars in religious studies, theology, philosophy, sociology, anthropology, psychology, history, and cultural and gender studies.